In Vivo Manganese–MR Imaging of Calcium Influx in Spontaneous Rat Pituitary Adenoma - Cross, D.J.; Flexman, J.A.; Anzai, Y.; Sasaki, T.; Treuting, P.M.; Maravilla, K.R.; Minoshima, S. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Rapid uptake of the calcium analog manganese (Mn2+) into spontaneous pituitary adenoma during MR imaging of aged rats generated the hypothesis that neuroendocrine tumors may have a corresponding increase in calcium influx required to trigger hormonal release. A goal of this study was to investigate the potential for clinical evaluation of pituitary adenoma by MR imaging combined with administration of Mn2+ (Mn-MR imaging).MATERIALS AND METHODS: Mn-MR imaging was used to characterize the dynamic calcium influx in normal aged rat pituitary gland as well as spontaneous pituitary adenoma. To confirm the validity of Mn2+ as a calcium analog, we inhibited Mn2+ uptake into the olfactory bulb and pituitary gland of normal rats by using the calcium channel blocker verapamil. Rats with adenomas received fluorodeoxyglucose–positron-emission tomography (FDG-PET) scanning for characterization of tumor metabolism. Mn2+ influx was characterized in cultured pituitary adenoma cells.RESULTS: Volume of interest analysis of the normal aged pituitary gland versus adenoma indicated faster and increased calcium influx in adenoma at 1, 3, 11, and 48 hours. Mn2+ uptake into the olfactory bulb and pituitary gland of normal rats was inhibited by calcium channel blockers and showed dose-dependent inhibition on dynamic MR imaging. FDG-PET indicated correlation between tumor energy metabolism and Mn2+ influx as well as tumor size.CONCLUSION: These results indicate that adenomas have increased activity-dependent calcium influx compared with normal aged pituitary glands, suggesting a potential for exploitation in the clinical work-up of pituitary and other neuroendocrine tumors by developing Mn-MR imaging for humans.